Key themes for the global energy economy in 2022 - The Oxford Institute for Energy Studies (The Oxford Institute for Energy Studies, 2022)
This paper contains 20 short articles which outline the views of OIES research fellows on some of the key themes for the global energy economy in 2022. Starting with views on the short-term outlook for oil, electricity and gas markets, the articles move on to cover LNG supply and Russian export strategy as well as the future of the Nord Stream 2 pipeline. The majority of the articles, though, are on issues around the energy transition, looking at the key milestones ahead of COP27 but also considering many of the most important topics discussed at COP26 where action now needs to be taken. These include the Global Methane Pledge, the development of voluntary carbon markets, the prospects for hydrogen projects, the building of a business case for CCUS and the need to update country NDCs in the next 12 months. The paper also looks at regional developments in the EU, India and China, and considers a number of legislative and regulatory topics that are likely to dominate environmental policy making in the energy sector during 2022.
Keywords: 330; CCUS; China; COP27; Electricity; Energy Transition; EU; Gas; Hydrogen; India; Methane; Oil